PENGARUH EKSTRAK DAUN KENIKIR (Cosmos caudatus Kunth.) TERHADAP MORTALITAS KUTU BERAS (Sitophilus oryzae L.) - Hidayat, Saleh (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
Rice louse (Sitophilus oryzae L.) is kind of insect wich damage agricultural crop. The rice damage can prevent with nature pesticide of marble leaf extract (Cosmos caudatus Kunth.). This research used experiment method with Completely Randomized Design (CRD) with 5 treatments and 5 replications. The result of this research proof that: 1) Giving marble leaf extract in such concentrations (20 gram marble leaf extract/100gram rice, 40 gram marble leaf extract/100 gram rice, 60 gram marble leaf extract/100 gram rice, and 80 gram marble leaf extract/100 gram rice) show real influence than rice louse mortality (Sitophilus oryzae L.) which show significant result is 0,000 < 0,005. 2) The result of this research is P4 extract doses (80 gram marble leaf extract/100 gram rice) show increasing higher to the rice louse mortality, So giving marble leave extract show real influence to rice louse mortality.Â Key words: marble leaf extract concentrations, mortality level, rice louse